Pembelajaran Tafsir Al Qur’an sebagai Upaya Peningkatan Ekstrakurikuler Keagamaan Peserta Didik: Kajian Teoritis dan Implementasinya - Putri Firdaus Fahmi; Joko Subando (Lembaga Yasin AlSys, 2026)
Qur’anic exegesis learning has become an important part of the Islamic educational tradition, particularly in Islamic educational institutions and Islamic boarding schools. However, studies on the implementation of Qur’anic exegesis learning in students’ extracurricular activities within general education settings remain limited. This study aims to examine Qur’anic exegesis learning theoretically and to explain its implementation in religious extracurricular activities in general education units. This study used a library research approach with a descriptive-analytical design through the examination of various relevant literature on Qur’anic learning, exegesis, religious education, and extracurricular activities. The findings show that Qur’anic exegesis learning can support the strengthening of students’ religious extracurricular activities because it provides a deeper understanding of the content of Qur’anic verses, Islamic values, and the formation of religious attitudes in daily life. These findings confirm that exegesis learning is not only relevant to be applied in Islamic boarding schools or Islamic educational institutions but can also be developed within the scope of general education through structured extracurricular activities. The implications of this study provide a theoretical contribution to the development of literature on Qur’anic learning in general education settings and open opportunities for further research on the models, strategies, and effectiveness of Qur’anic exegesis learning in students’ extracurricular activities.